Spin-Orbit Angles as a Probe to Orbital Evolution. Issue Volume 8:Issue S299(2013) (6th January 2014) - Triaud, A. H. M. J.; Cameron, A. Collier; Queloz, D.; Anderson, D. R.; Brown, D. J. A.; Smalley, B.; Bouchy, F.; Lendl, M.; Gillon, M.
Abstract: We observed with HARPS, the Rossiter-McLaughlin effect for 40 of the 75 transiting hot Jupiters discovered in the Southern Hemisphere by WASP. Our observations reveal a wide distribution in orbital inclinations indicative of past dynamical interactions. Our data also demonstrate the important effect produced by tidal interactions in shaping the spin–orbit (β) angle distribution. We briefly present and interpret the data we collected in a series of graphs.